Meristic counts, morphometric characters, and length-weight of Megalaspis cordyla (Linnaeus, 1758) along the west coast Peninsular Malaysia - Sobari, Mohd Akmal; Mohamed, Rozihan; B., Akbar John (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
This study describes the meristic counts, morphometric characters, and length-weight relationship of Megalaspis cordyla along west coast Peninsular Malaysia. Seven meristic counts and twenty-three morphometric characters have been studied form each fish specimens collected from Kuala Selangor, Kuala Gula and Kuala Kedah. The specimens ranging from 217.9 to 381.5 mm in total length and 125.0 to 497.0 g in body weight were analysed in this study. The meristic counts and morphometric characters were not significantly different between three locations. The length-weight relationship was calculated as W = 0.0196L2.7956. The coefficient of determination (r2) for the length and weight relationship was estimated at 0.9498 indicating high degree of correlation between the two parameters. The condition factor varied from 0.79 to 1.22.